SOSIALISASI DAN PENDAMPINGAN PENYIAPAN MATERIAL KONSTRUKSI PERKERASAN LENTUR JALAN RAYA KEPADA SUPPLIER - Gon, Kasmir; Caling, Claudius Lippershey Bright; Ode, Yohanes Leonardo Noveri; Marseven, Agustinus; Avendri, Yohanes Leonardus (Jurnal Abdimas Bina Bangsa, 2025)
This PkM will be implemented on 12 – 13 April 2024 with the aim of increasing knowledge and skills as well as legal awareness, productivity and the economy of PkM partners. This PkM has fostered legal awareness, increased knowledge and skills of PkM participants, as can be seen from the competency evaluation of PkM participants who before the socialization have zero score, increased to an average of 77 and inreased to 80 after mentoring. The Bondo quary material quaified as the embankment for flexible highway pavement because the soil is of type ML (USCS) and type A-1-a (0) according to AASHTO, active value of 0.90 < 1.25 categorized as normal soil, CBR soaked for 96 hours is 24% > 10%. Doesn’t qualify as aggregate A because material passes the 1½” sieve < 100% and the soaked CBR < 90%. Doesn’t qualify as aggregate B because soaked CBR is 24% < 60%.